COLOCVIALNI ABBREVIATIONS IN INTERNETCOMMUNICATION: CLASSIFICATION, CHARACTER OF ADAPTATION BY UKRAINIAN-LANGUAGE DISCOURSOM - Golodyuk, Ya. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article an attempt is made to determine colloquial abbreviations, classify them according to their structure and type of abbreviation, discover peculiarities of their adaptation to Ukrainian-language discourse of Internet communication.